A new allele of human alpha1-antitrypsin: PiNhampton. - Arnaud, P (1978)
A new allele of alpha1AT is described. By isoelectric focusing, the microheterogeneous pattern of the variant was similar to but more cathodal than that of Pi N. This allele has therefore been tentatively designated PiNhampton(Nham). Further examination revealed that the minor bands of Nham are indistinguishable from the major bands of Z by isoelectric focusing, and a careful family study was necessary to clearly define the proband's phenotype. Pi Nham was found in association with M1, S, and Z, but to date its possession is not apparently related to clinical disorders or reduced serum levels of alpha1AT.